Women's health-related vulnerabilities in natural disaster-affected areas of Bangladesh: a mixed-methods study protocol. Issue 11 (24th November 2020) - Riyad Fatema, Syadani
Abstract : Introduction: Global climate change has produced growing natural disasters across the world especially in Global South. Different countries experience varied vulnerabilities depending on their geographical location, economic status and ability of management. In a highly disaster susceptible developing country like Bangladesh, many individuals experience a greater rate of natural disasters with devastating health effects. Compare with men, women have a higher incidence of mortality and health effects following natural disasters. The study aims to explore women's experience of physical and psychological health vulnerabilities with primary causes in natural disaster-affected areas of Bangladesh. Methods and analysis: This is an exploratory mixed-method study comprising survey and in-depth interviews with equal priority to identify physical and psychological health vulnerabilities of women living in natural disaster-affected areas of Bangladesh. Quantitative data will be collected using self-administered sociodemographic and perceived severity instrument, 12-item Short-Form, Impact of Event Scale-Revised and Brief Coping Scale, while specific open-ended guidelines will be used for the qualitative part. The instruments will be translated into Bangla following the Brislin (1970) model of translation. The survey will be administered in paper copies, with at least 384 respondents, whereas 30 participants will be in-depth interviewed using an audio recorder. Survey data will be analysed using SPSS V.25 following descriptive and inferential statistics as required. The recorded open-ended responses will be transcribed and analysed using thematic analysis. Finally, both data sets will be integrated and synthesised according to the sequential mixed-method approach. Ethics and dissemination: The study has been reviewed and approved by the Human Research Ethics Committee of the University of New England. The results will be actively disseminated through peer-reviewed journals, conference presentations, social media, the internet and various community engagement activities.